2014
DOI: 10.1107/s1399004714005331
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the phosphotransferase domain of the bifunctional aminoglycoside-resistance enzyme AAC(6′)-Ie-APH(2′′)-Ia

Abstract: The bifunctional acetyltransferase(6')-Ie-phosphotransferase(2'')-Ia [AAC(6')-Ie-APH(2'')-Ia] is the most important aminoglycoside-resistance enzyme in Gram-positive bacteria, conferring resistance to almost all known aminoglycoside antibiotics in clinical use. Owing to its importance, this enzyme has been the focus of intensive research since its isolation in the mid-1980s but, despite much effort, structural details of AAC(6')-Ie-APH(2'')-Ia have remained elusive. The structure of the Mg2GDP complex of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 64 publications
(92 reference statements)
3
13
0
Order By: Relevance
“…B. Representative example of recent crystal structures for AACs (AAC(6′)-Ie as yellow cartoon with KANA as navy stick; PDB code 4QC6; 148 from the bifunctional enzyme AAC(6′)-Ie/APH(2″)-Ia), APHs (APH(2″)-Ia as dark blue cartoon with GDP as orange stick; PDB code 4ORK; 144 from the bifunctional enzyme AAC(6′)-Ie/APH(2″)-Ia), ANTs (ANT(2″)-Ia as green cartoon with KANA as navy stick; PDB code 4WQL; 145 normally a monomer), and Eis as pale blue cartoon with CoA as yellow stick and TOB as red stick (PDB code 4JD6; 127 normally an hexamer) resistance enzymes. Note : Only the monomer of each of these enzymes is shown.…”
Section: Figmentioning
confidence: 99%
“…B. Representative example of recent crystal structures for AACs (AAC(6′)-Ie as yellow cartoon with KANA as navy stick; PDB code 4QC6; 148 from the bifunctional enzyme AAC(6′)-Ie/APH(2″)-Ia), APHs (APH(2″)-Ia as dark blue cartoon with GDP as orange stick; PDB code 4ORK; 144 from the bifunctional enzyme AAC(6′)-Ie/APH(2″)-Ia), ANTs (ANT(2″)-Ia as green cartoon with KANA as navy stick; PDB code 4WQL; 145 normally a monomer), and Eis as pale blue cartoon with CoA as yellow stick and TOB as red stick (PDB code 4JD6; 127 normally an hexamer) resistance enzymes. Note : Only the monomer of each of these enzymes is shown.…”
Section: Figmentioning
confidence: 99%
“…According to the structure model, the first DxD motif (aa 31-33) is located in the same cavity as the P-loop and thus more likely to participate in the NTP-binding and hydrolysis. GAR is shorter than other aminoglycoside phosphotransferases (APHs) and seems to contain five N-terminal parallel β-sheets, while APHs contain five anti-parallel β-sheets in their N-terminal domain [24,25] worrying, since the newest semisynthetic aminoglycoside plazomicin (FDA-approved for treatment of complicated urinary tract infections [39]), which is derived from sisomicin and designed to avoid most of the common AMEs [40], includes garosamine. In the light of more and more widespread resistance to e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Rigid-body modeling suggested that the AAC and APH domains were oriented such that the substrate-binding sites were adjacent to one another. More recently, the structure of the APH(2 00 )-Ia domain of the bifunctional enzyme was reported as the Mg 2 GDP complex (Smith et al, 2014). Here, we report the structure of the ternary kanamycin/coenzyme A complex of the AAC(6 0 )-Ie domain of this enzyme refined at 1.3 Å resolution.…”
Section: Introductionmentioning
confidence: 89%
“…Rigid-body modeling calculations for the bifunctional enzyme using the crystal structures of AAC(6 0 )-Ie presented here and the recently reported APH(2 00 )-Ia structure (Smith et al, 2014) connected by a flexible linker of variable length were performed using CORAL (Petoukhov et al, 2012). A series of ten calculations were run with each of the linker lengths (zero, six, eight, ten and 12 residues) and repeated for three different starting orientations.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%